'A kind of useless man'? An evaluation of AIF cooks and cookery, 1914–1918. (April 2022) - Reynaud, Daniel; Reynaud, Emanuela
While the Australian Imperial Force of 1914–1918 experienced a significant shift from amateurism to professionalism over the course of the war in most areas, one crucial role not yet examined in the literature on the Australian Imperial Force is that of army cook. This article argues that their role was not taken sufficiently seriously during the Great War, leaving them effectively still amateurs at the end of the war. It explores the regulations for army cooks, the processes of selection, training and monitoring, as well as their performance in camps and in the field, and draws the conclusion that the army failed to professionalize role.